Low temperature photoluminescence, transient photoconductivity and microwave reflection for optical properties and transport in PLD-GaN - Niehus, M.
Optical and transport data on GaN samples grown by low-temperature pulsed laser deposition are presented. Large below-gap band tails are observed in optical absorption spectroscopy. The most intense photoluminescence lines of medium crystalline quality samples can be attributed to excitons bounded to stacking faults. The samples of the highest quality show, besides the ubiquitous yellow band, a large near band emission (NBE) peaking at 3.47 eV. The large width of the NBE is attributed to the joint effects of the band tails and an elevated carrier concentration. Secondary photocurrent transients show a slow decay reaching the millisecond time region for a variety of excitation wavelengths and intensities, with a power law decay exponent of around -0.3. The long times are attributed to the trapping of excess carriers in extended band tail states. From the comparison of photocurrent decay with excess carrier-induced microwave reflection it is concluded that the decay dynamics at the air/film and film/substrate interfaces are identical. © 2002 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.